Effect of vitamin D supplementation on training adaptation in well-trained soccer players - Jastrzebska, M.; Kaczmarczyk, M.; Jastrzebski, Z. (The Journal of Strength and Conditioning Research, 2016)
There is growing body of evidence implying that vitamin D may be associated with athletic performance, however, studies examining the effects of vitamin D on athletic performance are inconsistent. Moreover, very little literature exists about the vitamin D and training efficiency or adaptation, especially in high-level, well-trained athletes. The purpose of the current study was to investigate the effect of vitamin D supplementation on training adaptation in well-trained football players. The subjects were divided into 2 groups: the placebo group (PG) and the experimental group (SG, supplemented with vitamin D, 5,000 IU per day). Both groups were subjected to High Intensity Interval Training Program. The selection to the groups was based on peak power results attained before the experiment and position on the field. Blood samples for vitamin D level were taken from the players. In addition, total work, 5, 10, 20, and 30 m running speed, squat jump, and countermovement jump height were determined. There were no significant differences between SG and PG groups for any power-related characteristics at baseline. All power-related variables, except the 30 m sprint running time, improved significantly in response to interval training. However, the mean change scores (the differences between posttraining and pretraining values) did not differ significantly between SG and PG groups. In conclusion, an 8-week vitamin D supplementation in highly trained football players was not beneficial in terms of response to High Intensity Interval Training. Given the current level of evidence, the recommendation to use vitamin D supplements in all athletes to improve performance or training gains would be premature. To avoid a seasonal decrease in 25(OH)D level or to obtain optimal vitamin D levels, the combination of higher dietary intake and vitamin D supplementation may be necessary.